Comparison between asphalt rubber and conventional mixtures in overlay design - Fontes, Liseane P. T. L. (2008)
Asphalt modified with crumb rubber has been used to produce asphalt rubber mixtures for pavement overlays subjected to heavy loads and high temperatures. Under severe conditions, these mixtures are capable of resisting permanent deformations, having an extended fatigue life and resisting crack propagation in comparison to conventional ones. A laboratory research was conducted to determine the performance properties of overlays with asphalt rubber mixtures produced through wet processes using a gap graded mixture. The asphalt rubber was prepared by the continuous blend process and its properties were measured by means of current tests. An identical study for a conventional mixture used as a reference was performed. An extensive study in which the mechanical properties of the studied mixtures were determined and compared was also carried out. The permanent deformation and the fatigue test of two different mixture designs manufactured with modified and conventional binders, with the same aggregates and different binder contents, were evaluated. The mechanical results from asphalt rubber and conventional mixtures were also compared by applying a pavement overlay design method that considers crack propagation from the existing pavement to the pavement overlay.